A Novel Tension Machine Promotes Bone Marrow Mesenchymal Stem Cell Osteoblastic and Fibroblastic Differentiation by Applying Cyclic Tension. (10th August 2021) - Zhao, Yi; Huang, Yiping; Jia, Lingfei; Wang, Ruoxi; Tan, Kuang; Li, Weiran
Abstract : Bone marrow mesenchymal stem cells (BMSCs) are intraosseous stem cells, and the effects of tensile strain on BMSC differentiation mediate several bone-related treatments. To study the response of BMSCs under tension, we designed and developed a small cellular tension instrument, iStrain. When iStrain applied tension on BMSCs, these cells exhibited convergence in the alignment direction and lengthening of the cell processes and cell body. Real-time quantitative polymerase chain reaction (RT-qPCR) and western blotting demonstrated that iStrain-mediated cyclic tension promotes the differentiation of BMSCs toward osteogenesis and fibrogenesis. And the mRNA and protein expression of differentiation-related genes changes with the extension of tension time.